Using Fairy Tale In Enhanced Spelling Learning of First High School Student In The City Of Manado - Monoarfa, S (Universitas Negeri Manado, 2019)
. The problem with this research is that teachers in teaching students focus more on improving teaching methods. They are more interested in choosing learning strategies such as inquiry, STAD, jigsaw, learning cell, and so on that emphasize the application of learning steps. The teachers forget their role as facilitators and creators who always facilitate students with teaching materials / materials as a result of the creation of teachers that have an impact on learning outcomes that are less than optimal. To solve this, the teacher needs to prepare a reading